2001
DOI: 10.1007/s002800000187
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of deguelin, a cancer chemopreventive agent in rats

Abstract: An initial pharmacokinetic investigation of deguelin showed that this rotenoid has a relatively long MRT and half-life in plasma in the rat. The compound distributed in the tissues and excreted as metabolites, mainly via the feces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 0 publications
2
44
0
Order By: Relevance
“…53 The results of this study showed that 10 À6 M deguelin is achievable in a variety of tissues in vivo after intravenous delivery. Moreover, this dosage is not toxic to rats.…”
Section: Discussionmentioning
confidence: 81%
“…53 The results of this study showed that 10 À6 M deguelin is achievable in a variety of tissues in vivo after intravenous delivery. Moreover, this dosage is not toxic to rats.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, the insecticidal activity of deguelin and other rotenoids and the systemic toxicities, such as neurological toxicities including somnolence and ataxia (38) are probably due to the potent inhibition of NADH-dehydrogenase and concomitant depletion of intracellular ATP. Deguelin has shown an IC 50 as low as 33 nM for NADH-dehydrogenase.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed for the first time that the antiproliferative, proapoptotic, and antiinvasive effects of deguelin may be mediated through the suppression of NF-B and NF-B-regulated gene products. Considering the pharmacologic safety of deguelin (64), this agent should be further explored as a potential chemopreventive agent.…”
Section: Discussionmentioning
confidence: 99%